2010
DOI: 10.1128/jvi.01805-09
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Administration of Bacterially Derived Immunomodulators Improves the Outcome of Influenza Virus Infection in a Murine Model

Abstract: Prophylactic or therapeutic immunomodulation is an antigen-independent strategy that induces nonspecific immune system activation, thereby enhancing host defense to disease. In this study, we investigated the effect of prophylactic immunomodulation on the outcome of influenza virus infection using three bacterially derived immune-enhancing agents known for promoting distinct immunological profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 83 publications
1
50
1
1
Order By: Relevance
“…In a similar approach, activation of TLR2/6 and TLR9 by pre-treatment with synthetic agonists reduced parainfluenza virus titres in guinea pigs; however, this regimen was not able to prevent virus-induced airway hyperreactivity (Drake et al, 2013). Similar to the immunostimulatory effect of individual TLR agonists, innate immune imprinting by local application of modified heat-labile Escherichia coli toxins has been shown to confer protection against respiratory viral infection in murine models (Norton et al, 2010;Williams et al, 2004). The need for local application might even be circumvented by dietary intake of probiotics, specifically those bacterial strains that trigger type I IFN production by plasmacytoid DCs (Jounai et al, 2015).…”
Section: Direct Interactions Of Bacteria and Viruses: Altered Virulenmentioning
confidence: 91%
“…In a similar approach, activation of TLR2/6 and TLR9 by pre-treatment with synthetic agonists reduced parainfluenza virus titres in guinea pigs; however, this regimen was not able to prevent virus-induced airway hyperreactivity (Drake et al, 2013). Similar to the immunostimulatory effect of individual TLR agonists, innate immune imprinting by local application of modified heat-labile Escherichia coli toxins has been shown to confer protection against respiratory viral infection in murine models (Norton et al, 2010;Williams et al, 2004). The need for local application might even be circumvented by dietary intake of probiotics, specifically those bacterial strains that trigger type I IFN production by plasmacytoid DCs (Jounai et al, 2015).…”
Section: Direct Interactions Of Bacteria and Viruses: Altered Virulenmentioning
confidence: 91%
“…In vivo and in vitro studies with LT show its capacity to enhance IL-23 and IL-1α production from DCs by activating extracellular signal-regulated kinase (ERK), mitogen-activated protein kinase (MAPK), and IL-1β secretion through a mechanism involving caspase-1 and the NLRP3 inflammasome (Brereton et al, 2011). Our own studies showed that pulmonary delivery of dmLT to mice results in elevated numbers of APCs with increased expression of CD80 (Norton et al, 2010). More recent publications confirm the direct interaction of CT with dendritic cells in vivo; using GM1-deficient mice it was shown that oral adjuvanticity required expression of the CT ganglioside receptor on hematopoietic cells but not on epithelial cells .…”
Section: Interactions Of Ct and Lt With Immune Cellsmentioning
confidence: 94%
“…Several studies, including ours, have demonstrated the important protective role of IL-17 against lethal flu infection. 12,13,41 In contrast, other groups have showed that IL-17 signaling was not required for viral clearance, but rather, played a pathogenic role by recruiting neutrophils to the site of inflammation. 16,42,43 These apparent discrepancies may be reconciled by strain differences between the various mouse models and subtypes/strains of influenza virus used in this work versus previous studies.…”
Section: Role Of Il-17 In H5n1 Influenza Virus Infectionmentioning
confidence: 83%